Hemocytes in Myriapoda (Arthropoda): a review - WER Xylander (Invertebrate Survival Journal, 2009)
Hemocyte types described in the different subtaxa of Myriapoda are presented and characterised. They comprise (1) prohemocytes, (2) plasmatocytes and (3) two different forms of granular hemocytes; these three have been found in all taxa investigated. Spherulocytes and coagulocytes were only found in some taxa. Adipohemocytes occur quite infrequent, oenocytoids have not been detected but may be restricted to specific stages of the moulting cycle. Cystocytes described earlier seem to be a preparation artefact. Granular hemocytes are the most frequent hemocytes followed by the plasmatocytes. In general, Diplopoda have fewer hemocytes than Chilopoda. The differences in the hematogram and the functions of hemocytes are discussed.